The Features of Audiovisual Structure in Films with Jazz and Pre-jazz Music - Kovalenko, Yuliia (Journal of History Culture and Art Research, 2019)
The purpose of this research is to consider the way of interaction between jazz and pre-jazzy music and screen for birth of new features and meanings, as well as to analyze the audiovisual structure in terms of jazzy expressive means. As time arts, music and cinema are closely related due to the fact that musical composition and film exist for a clearly period of time. Therefore, similar processes may arise on the basis of compositional patterns and artistic means, which generate an active exchange for achieving a new quality and the birth of unique phenomenon. Since modern art shows that different types of art today are aimed at mutual interaction and the creation of new combined forms, and cinema itself is one such a hybrid art, this interaction does not go unnoticed for those types of art that are involved in multi-artistic forms. No wonder different directions of music, styles and spheres of musical art affect the expressive structure of various movie genres. Among them films with jazz music occupy a special place having their own system of interaction between the two arts. This interchange is focused in such aspects as timbre heterogeneity as a reason for vividness of the plot lines and narrative variability, the ratio of improvisation and composition as two opposite beginnings in jazz and films involving jazz, compositional and structural principles of jazz as a method of dramatic narrative in films with jazz, the language and expressive means of jazz and their interaction with dramatic narrative in films and the influence of jazz on genre formation in cinema.